Ćwiczenie 1.
Wykonaj mnożenie. Odpowiedź podaj w najprostszej postaci.
e) [tex]\frac{(x-2)^2}{x^2+4x+4} * \frac{2+x}{x^2-4} = ?[/tex]

f) [tex]\frac{3x^2-x^3}{2x-6} * \frac{x^2+2x+1}{x^4-x^2} = ?[/tex]


Odpowiedź :

[tex]e) \ \frac{(x-2)^{2}}{x^{2}+4x+4} \cdot\frac{2+x}{x^{2}-4} = \frac{(x-2)^{2}}{(x+2)^{2}}\cdot\frac{x+2}{(x+2)(x-2)} = \frac{x-2}{(x+2)^{2}}\\\\Z: \ \ x\neq -2 \ \ i \ \ x\neq 2[/tex]

[tex]f) \ \frac{3x^{2}-x^{3}}{2x-6} \cdot\frac{x^{2}+2x+1}{x^{4}-x^{2}} = \frac{x^{2}(3-x)}{2(x-3)}\cdot\frac{(x+1)^{2}}{(x^{2}+x)(x^{2}-x)} =\frac{-x^{2}(x-3)}{2(x-3)}\cdot\frac{(x+1)^{2}}{x(x+1)(x+1)(x-1)}=\\\\=-\frac{x}{2(x-1)}\\\\Z: \ \ x \neq -1 \ \ i \ \ x\neq 0 \ \ i \ \ x\neq 1 \ \ i \ \ x\neq 3[/tex]